RELATIONSHIP BETWEEN PSYCHOLOGICAL CAPITAL MINDFULNESS AND SUBJECTIVE WELLBEING AMONG POST GRADUATE DOCTORS - khan, Kainat; Abbas, Saleem; Kainat, Tuba; Abdullah, Hina (International Research Journal of Social Sciences and Humanities, 2024)
The purpose of the present was to measure the relationship between Psychological Capital, Mindfulness and Subjective Wellbeing among Postgraduate Doctors. After detailed literature reviews following hypotheses were formulated 1). There would be positive relationship between Psychological Capital and Mindfulness among doctors, 2). There is likely to be that Psychological Capital, Mindfulness and would differ across gender among doctors. The sample of this study was consisted on 200 medical doctors including 100 male medical doctors and 100 female medical doctors. The data was collected from the different private and government hospitals located in Faisalabad. There is no specific age range and the population of the study males & females Postgraduate Doctors of different age group of Faisalabad Hospitals. Psychological capital, mindfulness attention awareness, psychological well-being scale use as instruments in the study. T-Test, Correlation, Regression, was used for data analysis. Results shows significant relationship finding of our both hypotheses. At the end of the implementation of the study, suggestions and recommendation were discussed in detail.